Development of advertising electronic edition of «PrintHouse» publishing office - Животкова, Елена Александровна; Колесникова, Татьяна Анатольевна (Technology audit and production reserves, 2014)
As a result of solving theoretical and practical problems, an advertising and information edition of the «PrintHouse» publishing office with a local-network distribution was developed. Its main purpose lies in familiarizing customers with the enterprise provided services and prices. The user can simply download the application onto his/her hard disk (if that is a network distribution) or open the presentation CD. Upon the development of the EE (electronic edition), it was found that it is updateable, because it contains some data, which require updating at times (service prices). This means that the edition content requires frequent adjustments. Therefore, Web-mailing is the most appropriate way of its distribution. A small information scope of the edition (25 MB) also predetermined the choice of an electronic distribution. CD formats of the project will be also brought into edition, but serving, however, as special cases of familiarization with actual offers and current prices of the publishing office. Thus, the developed software can be implemented as the publishing office advertising module, distributed locally and by the network.